2022
DOI: 10.1186/s12889-022-14376-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between preterm births and socioeconomic development: analysis of national data

Abstract: Background The increasing prevalence of preterm birth, which is a global phenomenon, is attributable to the increased medical indications, artificial gestations, and some socioeconomic factors. This study was conducted to identify whether development and equality indices are associated with the incidence of preterm birth, specifically, spontaneous and elective preterm births. Methods This retrospective observational study comprised an analysis of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The association between payment method and preterm birth is a complex issue. Research has revealed that socioeconomic status can be a contributing factor to preterm birth, with women who lack insurance or have public insurance being more susceptible to preterm birth compared to those with private insurance ( 37 ). One possible explanation for this correlation is that women with lower incomes may encounter more obstacles in accessing healthcare services, including prenatal care, which can elevate the risk of preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…The association between payment method and preterm birth is a complex issue. Research has revealed that socioeconomic status can be a contributing factor to preterm birth, with women who lack insurance or have public insurance being more susceptible to preterm birth compared to those with private insurance ( 37 ). One possible explanation for this correlation is that women with lower incomes may encounter more obstacles in accessing healthcare services, including prenatal care, which can elevate the risk of preterm birth.…”
Section: Discussionmentioning
confidence: 99%